Subjective method of refractometry and depth of focus - Sergienko, Nikolai M.; Gromova, Anastasia; Sergienko, Nikolai (Journal of optometry, 2012)
To study the impact of the depth of focus on subjective refraction and distribution of myopic and hyperopic refractions. A total of 450 eyes of 305 subjects in the age range of 23–34 years were recruited for the study. A distribution of refractions was examined using a traditional method of the subjective refractometry on the basis of point-like posterior focus notion. Correction of the results was made on the assumption that the emmetropic eye retains high visual acuity when applying convex lenses with values which are fewer or equal to the depth of focus values. The following values of the depth of focus were used: ±0.55D, ±0.35D and ±0.2D for visual acuity 1.0, 1.5 and 2.0, respectively. Application of the traditional method of refractometry produced the following occurrence of refractions: hypermetropia 59.3%, myopia 22% and emmetropia 18.7%. After correction of the initial results of values of the depth of focus the distribution of refractions was as follows: hypermetropia 12.7%, myopia 22% and emmetropia 65.3%. The traditional method of subjective refractometry with application of trial lenses was developed on the basis of data of large optical aberrations and significant depth of focus which values should be taken into account during interpretation of results of subjective refractometry. Our data regarding to prevalence of emmetropic refraction falls in line with basic science provisions in respect of the physiology of the eye. Estudiar el efecto de la profundidad de foco en la refracción subjetiva y la distribución de los estados refractivos miópicos e hipermetrópicos. Para el estudio se incluyeron 450 ojos de 305 sujetos con un intervalo de edad de 23 a 34 años. Se examinó la distribución de estados refractivos utilizando un método tradicional de refractometría subjetiva sobre la base de la noción de foco posterior en forma de puntos. La corrección de los resultados se realizó asumiendo que el ojo emétrope conserva una alta agudeza visual al aplicar lentes convexas con valores inferiores o equivalentes a los valores de profundidad de foco. Se utilizaron los valores de profundidad de foco siguientes: ±0,55 D, ±0,35 D y ±0,2 D para una agudeza visual de 1,0, 1,5 y 2,0 respectivamente. La aplicación del método de refractometría tradicional produjo la incidencia de refracciones siguiente: hipermetropía 59,3%, miopía 22% y emetropía 18,7%. Tras la corrección de los primeros resultados de valores de profundidad de foco, la distribución de refracciones fue la siguiente: hipermetropía 12,7%, miopía 22% y emetropía 65,3%. El método tradicional de refractometría subjetiva con la aplicación de lentes de prueba se desarrolló basándose en datos de altas aberraciones ópticas y una profundidad de foco significativa, valores que deberían tenerse en cuenta a la hora de interpretar los resultados de refractometría subjetiva. Nuestros datos relativos a la prevalencia de refracción emétrope coinciden con las previsiones científicas básicas respecto a la fisiología del ojo.